1965
DOI: 10.1083/jcb.25.1.117
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Extracellular Space in Central Nervous Tissue by Freeze-Substitution

Abstract: It was attempted to preserve the water distribution in central nervous tissue by rapid freezing followed by substitution fixation at low temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(163 citation statements)
references
References 32 publications
(64 reference statements)
7
156
0
Order By: Relevance
“…Early studies by Van Harreveld and co-workers (Vanharreveld and Crowell, 1964;Vanharreveld et al, 1965) using a cold metal mirror freezing device demonstrated that brain tissue needed to be fast frozen in 30 sec after excision from a mouse and before the onset of cardiac arrest (an ~8 minute times scale). After this time, morphological deterioration was observed and it was reported that the tissue resembled chemically fixed specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies by Van Harreveld and co-workers (Vanharreveld and Crowell, 1964;Vanharreveld et al, 1965) using a cold metal mirror freezing device demonstrated that brain tissue needed to be fast frozen in 30 sec after excision from a mouse and before the onset of cardiac arrest (an ~8 minute times scale). After this time, morphological deterioration was observed and it was reported that the tissue resembled chemically fixed specimens.…”
Section: Discussionmentioning
confidence: 99%
“…*P , 0.05; ***P , 0.001. extracellular space consists of thin layers of interstitial medium separating neurons and glial cells, so that the synaptic cleft and its surroundings are mostly sealed from the chemical standpoint. The width of the thin sheets composing the interstitial extracellular space has been measured in the range of a few tens of nanometers (10-40 nm) (26)(27)(28). In choosing our model geometry, we aimed to capture the hindrance of diffusion in the perisynaptic extracellular space (29) and the relative compartmentalization of the extracellular space (30), but it is impossible to provide a stereotypic description of the interstitial space given that it exhibits great variability (26).…”
Section: Electrodiffusion Computational Modelingmentioning
confidence: 99%
“…We modeled electrodiffusion in the extracellular space according to Poisson-Nernst-Planck equations (24) and based the geometry of the synaptic surroundings on the robust observation that free extracellular space consists of a connected network of thin layers running between neurons and glial cells (26,27) (Fig. 7A, B).…”
Section: Vol 29 October 2015mentioning
confidence: 99%
“…Wide dissemination in extracellular spaces is an efficient and rapid mechanism of virus dissemination within the CNS but is more important in rapid progression of fixed strain of the rabies virus [51].…”
Section: Viral Spread To the Cnsmentioning
confidence: 99%